Repeated cocaine exposure dysregulates BDNF expression and signaling in the mesocorticolimbic pathway of the adolescent rat. (9th August 2019) - Caffino, Lucia; Giannotti, Giuseppe; Messa, Giulia; Mottarlini, Francesca; Fumagalli, Fabio
Abstract: Objectives: Long-term abstinence following cocaine exposure up-regulates brain-derived neurotrophic factor (BDNF) expression in the mesocorticolimbic pathway. Given the increased vulnerability to drug abuse typical of adolescence, we hypothesized that changes in BDNF expression may become manifest early after the end of cocaine treatment in the adolescent brain. Methods: Rats received cocaine injections from postnatal day 28 (PND28) to PND42 and the mesocorticolimbic expression of BDNF was measured by real-time PCR and Western blotting at PND43. Results: In the ventral tegmental area, BDNF-tropomyosin receptor kinase B (TrΚB) expression and phosphorylation are enhanced while the intracellular signaling is unaltered. In the nucleus accumbens (NAc) shell and core, BDNF and its signaling were down-regulated. In the prelimbic (PL) cortex, we found reduced BDNF expression and increased phosphoprylation of TrΚB, ERK and AKT. In the infralimbic (IL) cortex, increased BDNF expression was coupled with reduced activity and expression of its downstream targets. To evaluate the role of glutamate on BDNF-independent changes, we investigated the expression of the transporter GLT-1 and the activation of the NMDA receptor subunit GluN2B, which were both increased in the PL cortex while reduced in the IL cortex. Conclusions: Our results show that adolescent cocaine exposure modulates BDNF system early after treatment in the mesocorticolimbic pathway, identifying a complex but specific set of changes that could provide clues for treatment.